Ethnomathematical Exploration of Two-Dimensional Geometric Shapes in Mekongga Traditional House Architecture - Ully Hidayati; Irajuana Haidar; Dima Marillah (Universitas Papua, 2025)
Geometry is a fundamental branch of mathematics, yet many students struggle to comprehend it as they often perceive the subject as disconnected from real-world applications. In reality, geometric concepts are deeply embedded in daily life, particularly evident in traditional architecture. The Mekongga tribe of Southeast Sulawesi, Indonesia, exemplifies this connection through their culturally rich architectural heritage. However, ethnomathematical research on the Mekongga remains limited, despite its significant potential for enhancing contextual mathematics education. This study aims to address this gap by examining geometric shapes in Mekongiga traditional houses. This investigation also highlights the properties of each two- dimensional geometric form discovered. Data collection involved field observations, semi- structured interviews with traditional house guards, and photographic documentation of existing structures. Data analysis was carried out by identifying two-dimensional geometric shapes, focusing on the walls, roofs and stairs which were then visualized using GeoGebra. The findings reveal specific geometric shapes integrated throughout the architectural elements: isosceles triangles and trapezoids are prominent in the roof structure, rectangular shapes dominate the walls designs, and parallelograms are distinctly present in the staircase construction. The formal properties inherent in mathematical principles correspond directly with each two-dimensional geometric shape discovered in the traditional Mekongga houses. This research contributes to the field of ethnomathematics by highlighting how traditional cultural practices incorporate mathematics and suggests applications to connect academic content with students' cultural heritage, providing teachers with authentic contexts for teaching geometric concepts.